Biomechanical Testing Of Hip Protectors - D'raj, Joshua (Universiti Sains Malaysia, 2018)
The occurrence of osteoporotic fracture is an increasing trend yearly around the world. The main incidence of osteoporosis fracture was hip fracture. A hip protector is a specialized pad either hard or soft usually inserted into pants or the underwear. It is designed to protect the hip region to prevent hip fractures following a fall. The purpose of this study is to test the efficacy of hip protectors in preventing the occurrence of a hip fracture. An experimental rig was set up to replicate the parameters similar to an actual sideway fall from a standing height that is able to cause a hip fracture. Two types of hip protectors was tested namely the soft hip protector and the hard hip protector. The threshold force to cause a hip fracture is identified to be around 2.5 kN and the hip protectors is used to attenuate the impact force from the sideway fall preventing the hip from fracturing. Based on the results, all hip protectors was capable to attenuate the force and reduce the force received by the femur below the threshold for hip fracture. Soft hip protectors are found to attenuate more force compared to the hard hip protectors. The market hip protector (HipSaver) can attenuate 7.36% more impact force and the soft (LD45 polyethylene foam) hip protector attenuates 6.31% more impact force compared to the hard hip protector. The soft hip protectors are also more ergonomic due to its thin, lightweight and flexibility. In conclusion, hip protectors are an effective external alternative that can be used to reduce the occurrence of hip fractures and improve the lifestyle of osteoporotic patients.